Preventive policy and its role in facing the Corona pandemic (Covid 19) - Dalloul, Instr. Russell Faisal (The college of law and political science journal, 2023)
In light of the health and economic situation experienced by all countries of the world, including Iraq, which is represented by the spread of the Corona pandemic (Covid 19), which is characterized by instability and confusion. Let us know it clearly in all the different areas of life, especially the legislative aspect. Urgent measures were taken by my group to confront the repercussions of this epidemic, and in addition to these urgent measures, other preventive and precautionary measures against the Corona virus (Covid 19), and this was based on the rules of periodic announcement to the public. Health for the year 2005, and therefore the Corona epidemic affected many people, and I write about the concerns of the general penal policy related to criminalization and punishment in order to establish the necessary procedures and develop policies to prevent this epidemic.Keywords: preventive policy, quarantine, Covid-19, state of emergency, infection transmission, exposure to danger.